(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
Amidst a contemporary landscape marked by materialism and hedonistic pursuits fueled by Avidya, there arises an imperative to embrace karuna, manifested through universal humanistic values such as compassion. This research endeavors to probe how an empathetic comprehension of the self and others, rooted in Jnana philosophy, shapes the development of karuna. The study engaged 580 participants from Indian colleges (N=580), who completed three questionnaires: the revised Portrait Values Questionnaire (PVQ-RR), the Interpersonal Reactivity Index (IRI), and the Big Five Inventory. In our sample a strong positive association was unveiled between empathy and altruism-based self-transcendence values quadrant emphasizing the inherent relationship amongst karuna and jnana-based empathetic understanding. Furthermore, a comprehensive examination was conducted to assess various hypotheses concerning the strength of connections between empathy and universal values as per Schwartz’s refined value theory. The outcomes underscored a robust link between empathy and altruistic values that prioritize others’ well-being over personal gain. Additionally, hierarchical multiple regression analysis demonstrated that empathy significantly contributes to elucidating variance in Schwartz’s self-transcendence quadrant values, irrespective of personality traits. These findings offer significant insights into potential cultural variations in the Indian interpretation of the circular structure within the refined value model, underscoring the pivotal role of empathy within the Jnana framework and supporting the ’Empathy-Altruism Hypothesis’.